Reimund Bieringer and Didier Pollefeyt, Eds. Paul and Judaism: Crosscurrents in Pauline Exegesis and the Study of Jewish-Christian Relations - Stegman, S.J., Thomas D. (Studies in Christian-Jewish Relations, 2013)
No abstract is available.